2020
DOI: 10.1101/2020.06.24.169326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topoisomerase IB interacts with genome segregation proteins and is involved in multipartite genome maintenance inDeinococcus radiodurans

Abstract: 31Deinococcus radiodurans, an extremophile, resistant to many abiotic stresses including 32 ionizing radiation, has 2 type I topoisomerases (drTopo IA and drTopo IB) and one type II 33 topoisomerase (DNA gyrase). The role of drTopo IB in guanine quadruplex DNA (G4 DNA) 34 metabolism was shown in vitro. Here we report that D. radiodurans cells lacking drTopo IB 35 (∆topoIB) show sensitivity to G4 DNA binding drug (NMM) under normal growth conditions. 36 The activity of G4 motif containing promoters like mutL an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…FtsK/SpoIIIE DNA translocases are multidomain and multifunctional proteins that are part of bacterial cell divisome machinery (Mohone and Goley, 2020). In D. radiodurans, our earlier work showed the involvement of ParBs, TopoIB in genome segregation, and FtsZ, FtsA, and DivIVA in cell division (Maurya et al 2019, Modi et al 2014, Chaudhary et al 2019, Kota et al 2021). The co-immunoprecipitation results showed that drFtsK interacts with these proteins indicating its role in both these processes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…FtsK/SpoIIIE DNA translocases are multidomain and multifunctional proteins that are part of bacterial cell divisome machinery (Mohone and Goley, 2020). In D. radiodurans, our earlier work showed the involvement of ParBs, TopoIB in genome segregation, and FtsZ, FtsA, and DivIVA in cell division (Maurya et al 2019, Modi et al 2014, Chaudhary et al 2019, Kota et al 2021). The co-immunoprecipitation results showed that drFtsK interacts with these proteins indicating its role in both these processes.…”
Section: Discussionmentioning
confidence: 92%
“…The possible interaction of drFtsK with other deinococcal proteins of cell division like FtsZ, FtsA, and DivIVA, and genome segregation proteins like TopoIB, ParB2, ParB3, and ParB4 was monitored in surrogate E. coli by using the co-immunoprecipitation method. The recombinant pUT18 plasmids were already used in the earlier studies (Maurya et al, 2016, Maurya et al, 2018, Chaudhary et al, 2019, Kota et al, 2021) were transformed in E. coli BL21 (DE3) pLysS strain expressing Histidine tagged FtsK (pETFtsK). E. coli cells co-expressing histidine-tagged FtsK with T18-tagged protein in separate combinations were obtained at the log phase and cell-free extracts were prepared.…”
Section: Methodsmentioning
confidence: 99%